Significance of Engineering the Octahedral Units to Promote the Oxygen Evolution Reaction of Spinel Oxides - Zhou, Ye (Advanced materials (Deerfield Beach, Fla.), 2019)
© 2019 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.